Genome-wide characterization of FK506-binding proteins, parvulins and phospho-tyrosyl phosphatase activators in wheat and their regulation by heat stress - Suri, Anantika; Singh, Harpreet; Kaur, Kirandeep; Kaachra, Anish; Singh, Prabhjeet (Frontiers in Plant Science, 2022)
Peptidyl-prolyl cis-trans isomerases (PPIases) are ubiquitous proteins which are essential for cis-trans isomerisation of peptide bonds preceding the proline residue. PPIases are categorized into four sub-families viz., cyclophilins, FK506-binding proteins (FKBPs), parvulins and protein phosphatase 2A phosphatase activators (PTPAs). Apart from catalysing the cis-trans isomerization, these proteins have also been implicated in diverse cellular functions. Though PPIases have been identified in several important crop plants, information on these proteins, except cyclophilins, is scanty in wheat. In order to understand the role of these genes in wheat, we carried out genome-wide identification using computational approaches. The present study resulted in identification of 71 FKBP (TaFKBP) 12 parvulin (TaPar) and 3 PTPA (TaPTPA) genes in hexaploid wheat genome, which are distributed on different chromosomes with uneven gene densities. The TaFKBP and TaPar proteins, besides PPIase domain, also contain additional domains, indicating functional diversification. In silico prediction also revealed that TaFKBPs are localized to ER, nucleus, chloroplast and cytoplasm, while the TaPars are confined to cytoplasm and nucleus. The TaPTPAs, on the contrary, appear to be present only in the cytoplasm. Evolutionary studies predicted that most of the TaFKBPs, TaPars and TaPTPA genes in hexaploid wheat have been derived from their progenitor species, with some events of loss or gain. Syntenic analysis revealed the presence of many collinear blocks of TaFKBP genes in wheat and its sub-genome donors. qRT-PCR analysis demonstrated that expression of TaFKBP and TaPar genes is regulated differentially by heat stress, suggesting their likely involvement in thermal tolerance. The findings of this study will provide basis for further functional characterization of these genes and their likely applications in crop improvement.